Pengaruh Salinitas dan Konsentrasi Polimer Carboxymethyl Cellulose Terhadap Viskositas dan Adsorpsi pada Formasi Batu Pasir - Toripalu, Brian Adisty Kurniawan S; Ramadani N, Raul Ferdy; Sinurat, Daniel (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2025)
Enhanced Oil Recovery (EOR) is an advanced oil recovery method used to increase oil production from reservoirs after primary and secondary recovery stages are no longer able to produce oil optimally. Therefore, this study aims to analyze the effect of salinity and Carboxymethyl Cellulose (CMC) solution concentration variations on viscosity and adsorption characteristics in sandstone formations as part of evaluating the potential application of polymers in polymer injection methods in Enhanced Oil Recovery (EOR) technology. The research method was carried out through compatibility testing, viscosity measurement, and adsorption testing using CMC solutions at several variations of concentration and salinity levels with 50 mesh sandstone media. The results showed that an increase in salinity caused a decrease in the viscosity of the CMC solution. At a salinity of 5000 ppm, the viscosity was 4 cP, 4.82 cP, and 16.02 cP at concentrations of 5000 mg/L, 7500 mg/L, and 10000 mg/L, respectively. while at a salinity of 10,000 ppm, it decreased to 2.95 cP, 4.59 cP, and 10.07 cP. In the adsorption test, the adsorption value increased with increasing concentration and salinity. The adsorption values at a salinity of 5000 ppm were 5.13 mg/g, 7.63 mg/g, and 8.46 mg/g, respectively, while at a salinity of 10000 ppm, they increased to 6.32 mg/g, 9.36 mg/g, and 10.61 mg/g.